QUANTUM REALITY AND EDUCATION IN THE XXI CENTURY - Сухова, Н. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article tells about the philosophical problems of influence of modern scientific understanding of reality on changes in man's educational space.